ANALISIS KARAKTERISTIK BENTUK ALIRAN SUNGAI PANTAI BOKEK, DESA TANJUNG SELAMAT, KECAMATAN SUNGGAL, KABUPATEN DELI SERDANG, KOTA MEDAN - Ayu Fadhilla; Darwin P. Lubis (Jurnal Samudra Geografi, 2022)
The purpose of this study was to determine the Analysis of the Characteristics of the Bokek Coastal River Flow Form. The method used in this study is a qualitative method, with direct plunge and direct observation methods in the Bokek Beach River. The data collection technique used in this study was carried out with the stages of Observation and documentation taking pictures directly in the area. The results of research on the characteristics of the Bokek Beach river flow have a dendritic river flow pattern, because the flow pattern with river branches resembles a cross-sectional line or leaf reinforcement. Based on the profile of the Bokek Beach river, this is the downstream river, because the last part of the river, which will eventually lead the river to the sea (estuary). The movement of the Bokek Beach river flow is a type of turbulent motion caused by irregular water flow. There are large rocks and holes. These holes vary in size from a few centimeters to several decimeters.